Sustainable Recovery of SiO₂, Al₂O₃, and MgO from Slag, Aluminum Cans, and Bittern - Sukma, Vinda Avri; Sudibyo, Sudibyo; Wulandari, Yeni Ria; Ramandani, Adityas Agung; Dahlan, Astryd Viandila (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
This study investigates the utilization of solid waste from slag and aluminum cans as sources of valuable raw materials, along with bittern waste for magnesium oxide (MgO)cons production. Slag, a byproduct of industrial combustion in the palm oil industry, and aluminum cans, generated from human consumption in urban areas, were both subjected to leaching processes to recover silica (SiO₂) and alumina (Al₂O₃), respectively. The leaching of slag using 4 M NaOH yielded 85.68% SiO₂, while aluminum cans treated with 4 M HCl produced 85.90% Al₂O₃. Additionally, the study extracted MgO from bittern waste via precipitation, resulting in 76.98% MgO. X-ray fluorescence (XRF) analysis was employed used to determine the composition of the slag, aluminum can waste, and bittern, while X-ray diffraction (XRD) analysis confirmed the crystallinity of the recovered materials. The integration of recycled materials into the production of cordierite ceramics represents an innovative approach to waste valorization, offering potential for the development of advanced materials from industrial and urban waste. This research highlights the potential for valorizing industrial and municipal solid wastes through chemical processes, contributing to sustainable resource recovery and environmental conservation.